An Eclectic Theory of Entrepreneurship: Three level analysis for developing Entrepreneurship Policy in Pakistan - Shaheen, Dr. Nasir; Ahmad, Dr. Nasir; Hussain, Dr. Sajjad; Hussain, Dr. Badshah (The journal of contemporary issues in business and government, 2021)
The study was intended to recommend guidelines for developing entrepreneurship policy in Pakistan. For this purpose An Eclectic Theory of Entrepreneurship was used as theoretical frame work to analyze empirical research studies and available reports at three different levels. At micro level, low literacy rate was found to be foremost requirement for developing entrepreneurship. Lack of knowledge based economic system was found to be the center of problem at meso level. At macro level, core of the problem is that policy makers need to understand the spirit of entrepreneurship to plan economic policy accordingly. It was recommended that efforts may be made to: raise education level and entrepreneurial orientation of the people; reshaping to knowledge based economic system; and entrepreneurship may be designated as major pillar of economic policy.